A (trans)formação de oficiais da Polícia Militar de Sergipe - Tobias, Amanda Freitas dos Santos (2014)
In the last years, the studies on police formation have been growing dizzily. With the changes that occurred on the social and political plan especially after the promulgation of the Federal Constitution of 1988, the social claims grew for a more prepared police to guarantee the Democratic State of Rights. However, the recurrent episodes of police violence lead to questionings about how and what these professionals are formed for. As a crucial period for the socialization of the new members, the police formation occupies a privileged space on the debates about the issues that involve public security. In this context, the present paper analyses the part of the Officers Formation Course (OFC) in the process of transforming men and women into officers of the MPSE (Military Police of Sergipe). In this sense, questions were raised related to the identity and relations of gender, connected to the specificities of the exercise of the occupation military-police officer, seeking to understand how men and women live the process of becoming members of the police force, through the Officers Formation Course; how these professionals join to this logic of belonging and how the model of professional formation established by the institution exerts influence upon this process. It still matters comprehend what is the sense of being an officer of the MPSE for these professionals. Inspired in ethnomethodological studies, the search, of a qualitative order, used as main instrument the semi-structured interview. Ten officers were heard, five men and five women, formed by the academies to where the MPSE has sent more members to take the OFC course in the last twenty-five years, which are: Alagoas, Pernambuco, Bahia, Paraíba, Goiás e Rio de Janeiro.